Advances in periodic difference equations with open problems - Al-Sharawi, Ziyad (2014)
In this paper, we review some recent results on the dynamics of semi-dynamical systems generated by the iteration of a periodic sequence of continuous maps. In particular, we state several open problems focused on the structure of periodic orbits, forcing between periodic orbits, sharing periodic orbits, folding and unfolding periodic systems, and on applications of periodic systems.